تقييم استراتيجيات الفهم الشفهي لدى المتخلفين ذهنيا بدرجة بسيطة - قالى, جنات; جعلاب, محمد الصالح (جامعة الوادي - University of Eloued, 2022)
هدفت الدراسة إلى تقييم استراتيجيات الفهم الشفوي عند المتخلفين ذهنيا (درجة بسيطة) ،حيث استخدمت الدراسة منهج دراسة حالة على فئة قواهما 05 أطفال يعانون من تخلف ذهني درجة خفيفة ،تم اختيارهم بطريقة قصدية وذلك باستعمال نتائج اختبار الذكاء لكولومبيا الذي طبق على هذه الفئة من الأطفال من طرف المختص النفسي الخاص بالمركز النفسي البيداغوجي، كما طبقنا اختبار O52 وخلصت نتائج الدراسة إلى :كلما انتقلنا من استراتيجية بسيطة إلى الأكثر منها تعقيدا تقل نسبة الإجابات الصحيحة مما يدل على انخفاض في مستوى القدرات العقلية . Abstract: The study aimed at evaluating oral comprehension strategies for mentally retarded people (slight degree). The study used a case study method on a group of 05 children suffering from mild mental retardation, they were chosen intentionally, using the results of the Columbia IQ test, which was applied to this group of The children were appointed by the psychiatrist of the Pedagogical Medical Center, and we also applied the O52 test, and the results of the study concluded that: The more we move from a simple strategy to a more complex one, the lower the percentage of correct answers, which indicates a decrease in the level of mental abilities.
دراسة ميدانية بمركز المتخلفين ذهنيا لولاية أم البواقي
مقال
Keywords: التخلف الذهني ; الفهم الشفهي; Mental retardation - Oral comprehension